Micropropagation of dendrobium heterocarpum lindl. - Tham, Dang Thi; Bing, H’Yon Nie; Thanh Hang, Nguyen Thi; Khiem, Dinh Van; Duy, Nong Van; Vinh, Tran Thai; Hoi, Quach Van; Cong, Vu Kim (Vietnam Journal of Biotechnology, 2018)
Dendrobium heterocarpum Lindl. is an endangered species which is currently used as ornamental pot plant for its beautiful flowers. An increase in collection for trade or any other purposes may lead to a dramatic decrease in the population of this species, thus becoming rare or endangered species in the near future. In this study, effects of plant growth regulators (BA, NAA, IAA, IBA, TDZ) and natural supplements (carrot, potato, and banana extracts) on protocorm like bodies (PLBs) formation; growth and development of shoot; and root regeneration of D. heterocarpum Lindl. as well as type of substrates on acclimatization and growth of seedlings were investigated. The results showed that PLBs formation was optimal on MS medium supplemented with 2.0 mg/L BA and 1.0 mg/L NAA (7.11 PLBs/explant; PLBs formation percentage of 68.9%) or MS medium supplemented with 1 mg/L TDZ and 0.5 mg/L NAA (7.29 PLBs/explant; PLBs formation percentage of 75.53%). For subculture, MS medium supplemented 1.5 mg/L BA and 60 g/L banana extract (22.40 shoots/explant; shoot length of 2 cm) was the most suitable for shoot regeneration and growth. Additionally, root formation was the most suitable on ½ MS medium supplemented with 1 mg/L NAA (4.4 roots/shoot; root length of 3.12 cm; root formation of 95.56%). Finally, the sufficiently rooted plantlets were transferred to greenhouse for hardening. After 60 days, coconut fiber substrate was the most suitable for seedling growth and development (with survival rate of 97.78%, root number of 5 and shoot length of 3.4 cm). The results of propagation in vitro Dendrobium heterocarpum Lindl. contribute to conservation and sustainable development as well as towards the rapid multiplication of seedlings for commercial commercialization of this wild orchid species.